The social psychology of trauma : connecting the personal and the political - Muldoon, Orla (Cambridge University Press, 2024)
Many of us have been affected by trauma and struggle to manage our health and well-being. The social psychological approach to health highlights how social and cultural forces, as much as individual ones, are central to how we experience and cope with adversity. This book integrates psychology, politics, and medicine to offer a new understanding that speaks to the causes and consequences of traumatic experiences. Connecting the personal with the political, Muldoon details the evidence that traumatic experiences can, under certain conditions, impact people's political positions and appetite for social change. This perspective reveals trauma as a socially situated phenomenon linked to power and privilege or disempowerment and disadvantage. The discussion will interest those affected by trauma and those supporting them, as well as students, researchers, practitioners, and policy makers in social psychology, health and clinical psychology, and political science. This title is available as open access on Cambridge Core.